New species of Nereis (Annelida, Polychaeta, Nereididae) from Taiwanese waters - Hsueh, Pan-Wen (Zootaxa, 2020)
Members of Nereis species are characterised by having conical paragnaths on both maxillary and oral rings of the pharynx, and notopodial homogomph falcigers on posterior chaetigers. The present faunistic study includes Nereis species collected from various ecological surveys on coastal and offshore bathyal benthic habitats of Taiwan. The main results are that eight new species are described: N. articulata n. sp., N. longdongensis n. sp., N. nuwalianensis n. sp., N. paporae n. sp., N. shitipingensis n. sp., N. taitungensis n. sp., N. taiwanensis n. sp. and N. wuchiensis n. sp. In addition, two Nereis species are informally named as sp. A and sp. B because there was only a slightly poorly preserved specimen for each, although each species possess a unique combination of morphological characters that are not known from congeners reported from East Asia. A Table of key characters for all described species in the present study and a key to Nereis species from East Asia are provided.